Analisis Performa dan Studi Konsumsi Energi Kendaraan Listrik Sepeda Motor Listrik SEMOLI - Laksana, Nur Akhlis Sarihidaya; Ariawan, Radhi; Girawan, Bayu Aji; Sari Nurhidayat, Akhlis Rahman (Infotekmesin, 2024)
In this article the author conducts research related to energy consumption studies on electric motorbike vehicles (SEMOLI) made and developed by the author. The purpose of the energy consumption study is to determine the energy consumption of electric motorbike vehicles that have been made for further improvement and development. The method used is experimentation with the first phase testing on a straight flat road for one kilometer with flat road conditions, this phase of experimental results shows an average energy consumption of 30 Wh, for an average uphill road consumption of 40 km / h and for the second phase of experimental data using experimental methods with speed parameters 30 - 35 km energy consumption has an average of 30 Wh, at speeds of 40 - 45 km / h energy consumption has an average of 28 Wh, and 50-55 km / h average energy consumption of 27 Wh. The test results show that on flat road conditions and the increasing speed, the energy consumption will decrease.